Analysis of SARS-CoV-2 variants B.1.617: host tropism, proteolytic activation, cell–cell fusion, and neutralization sensitivity. Issue 1 (31st December 2022) - Zhang, Li; Li, Qianqian; Wu, Jiajing; Yu, Yuanling; Zhang, Yue; Nie, Jianhui; Liang, Ziteng; Cui, Zhimin; Liu, Shuo; Wang, Haixin; Ding, Ruxia; Jiang, Fei; et al.
ABSTRACT: SARS-CoV-2 has caused the COVID-19 pandemic. B.1.617 variants (including Kappa and Delta) have been transmitted rapidly in India. The transmissibility, pathogenicity, and neutralization characteristics of these variants have received considerable interest. In this study, 22 pseudotyped viruses were constructed for B.1.617 variants and their corresponding single amino acid mutations. B.1.617 variants did not exhibit significant enhanced infectivity in human cells, but mutations T478K and E484Q in the receptor binding domain led to enhanced infectivity in mouse ACE2-overexpressing cells. Furin activities were slightly increased against B.1.617 variants and cell–cell fusion after infection of B.1.617 variants were enhanced. Furthermore, B.1.617 variants escaped neutralization by several mAbs, mainly because of mutations L452R, T478K, and E484Q in the receptor binding domain. The neutralization activities of sera from convalescent patients, inactivated vaccine-immunized volunteers, adenovirus vaccine-immunized volunteers, and SARS-CoV-2 immunized animals against pseudotyped B.1.617 variants were reduced by approximately twofold, compared with the D614G variant.